Embryotoxic and teratogenic effects of styrene derivatives on sea urchin development. - Pagano, Giovanni; Esposito, Agostino; Giordano, Gian Giacomo; Hagström, Berndt E. (Scandinavian Journal of Work, Environment & Health, 1978)
The effects of styrene and some of its derivatives on the fertilization and differentiation of sea urchins was investigated. When one of the gametes was pretreated for a few minutes, it was ascertained that the test substances act on the haploid nucleus, producing specific changes in the differentiation of the embryo. By this test system directly acting, weak mutagens may be detected.
Keywords: development; embryotoxic effect; fertilization; mutagenicity; sea urchin; sea urchin development; styrene; styrene derivative; teratogenic effect